A miniature, low‐power scientific fluxgate magnetometer: A stepping‐stone to cube‐satellite constellation missions. Issue 12 (19th December 2016) - Miles, D. M.; Mann, I. R.; Ciurzynski, M.; Barona, D.; Narod, B. B.; Bennest, J. R.; Pakhotin, I. P.; Kale, A.; Bruner, B.; Nokes, C. D. A.; Cupido, C.; Haluza‐DeLay, T.; et al.
Abstract: Difficulty in making low noise magnetic measurements is a significant challenge to the use of cube‐satellite (CubeSat) platforms for scientific constellation class missions to study the magnetosphere. Sufficient resolution is required to resolve three‐dimensional spatiotemporal structures of the magnetic field variations accompanying both waves and current systems of the nonuniform plasmas controlling dynamic magnetosphere‐ionosphere coupling. This paper describes the design, validation, and test of a flight‐ready, miniature, low‐mass, low‐power, and low‐magnetic noise boom‐mounted fluxgate magnetometer for CubeSat applications. The miniature instrument achieves a magnetic noise floor of 150–200 pT/√Hz at 1 Hz, consumes 400 mW of power, has a mass of 121 g (sensor and boom), stows on the hull, and deploys on a 60 cm boom from a three‐unit CubeSat reducing the noise from the onboard reaction wheel to less than 1.5 nT at the sensor. The instrument's capabilities will be demonstrated and validated in space in late 2016 following the launch of the University of Alberta Ex‐Alta 1 CubeSat, part of the QB50 constellation mission. We illustrate the potential scientific returns and utility of using a CubeSats carrying such fluxgate magnetometers to constitute a magnetospheric constellation using example data from the low‐Earth orbit European Space Agency Swarm mission. Swarm data reveal significant changes in the spatiotemporal characteristics of the magnetic fields in the coupled magnetosphere‐ionosphere system, even when the spacecraft are separated by only approximately 10 s along track and approximately 1.4° in longitude. Key Points: The design, validation, and test of a purpose‐built miniature fluxgate magnetometer for cube‐satellite applications are presented Such a design enables scientifically valuable measurements from low‐cost multi‐cube‐satellite constellation missions Using Swarm data we illustrate the potential of using cube‐satellites for magnetosphere‐ionosphere coupling constellation missions